Single-dose diethylcarbamazine in the control of periodic brugian filariasis in Peninsular Malaysia - Hakim, S.L.; Vythilingam, I.; Marzukhi, M.I.; Mak, J.W. (1995)
The study compared the effectiveness of a single dose of diethylcarbamazine (DEC) (6mg/kg) with the standard regimen of 6 doses (total 36mg/kg) in mass chemotherapy for the control of brugian filariasis. Mass chemotherapy with single-dose DEC was instituted in one area and standard dose in the other and treatment was repeated after one year. Parasitplogical surveys were conducted before, and 3, 7 and 12 months after treatment. Pretreatment characteristics were not significantly different between the 2 treatment areas. There was a significant reduction in microfilaraemia prevalence rate from 24.7 to 14.7 at 12 months and to 6.8 at 19 months in the single dose area and from 22.8 to 9.6 at 12 months and to 2.7 at 19 months with the standard dose. Maximum reduction was at 7 months after treatment with both regimens. There was also significant progressive reduction in mean microfilarial density from 4.39 ± 20.37 to 0.89 ± 4.16 per 60 μL in the single-dose area and from 4.43 ± 17.31 to 0.75 ± 4.95 per 60 μL in the standard dose area. There was a greater reduction of both microfilarial prevalence and density using the standard regimen but it was not statistically significant. Thus, a single dose of DEC is as effective as the standard dose in controlling periodic brugian filariasis.